Theoretical and Experimental Investigations of the Rotor Vibration Amplitude of the Turbocharger and Bearings Temperature - E. Zadorozhnaya; S. Sibiryakov; V. Hudyakov (Tribology in Industry, 2017)
One of the most urgent issues of the modern world and domestic automobile and tractor production is the problem of the production of efficient and reliable turbochargers. The rotor bearings largely determine the reliable operation of the turbocharger. By increasing the degree of the forcing of the engine the turbocharger rotor speed and the load increases significantly. Working conditions of bearings also complicated because of the temperature rise. In this case the bearing of the turbine and the compressor bearing works in different thermal conditions. The definition of the thermal state of the bearings can be performed experimentally. However, to perform these studies the sophisticated experimental equipment must be used. Researchers can't perform experiments for each type of turbocharger. Therefore, the applying of the theoretical approaches becomes more relevant. The peculiarity of the considered problem is the design of the bearings, which are made in the form of multilayer bearings with floating rings. Such designs increase the number of the parameters that affect the behaviour of the rotor. For the calculation of the multilayer bearings and turbocharger rotor dynamics a method and calculation algorithm was developed. A plan of the experiment based on the orthogonal central composite plan was drawn up. The regression equations for rotor amplitude and bearing temperature were obtained. As variable parameters the clearances (external and internal), rotor speed, pressure and lubricant temperature were used. The results of the calculation were compared with experimental results obtained at the plant. Non-Newtonian properties of the lubricants were taken into account in the calculations. Comparative results showed good agreement. In this way the resulting function can be applied to studies of the similarly multilayer bearings without complicated experimental studies.